Gear Ratio Distribution of Electric Vehicle Reducer. (October 2020) - Tang, Zhihao; Li, Xinmin
Abstract: Based on the contact fatigue strength criterion of tooth surface, the mathematical model of gear ratio distribution of the electric vehicle is established. In the process, there are two objective functions. One is the minimum diameter of electric vehicle reducer, the other is the minimum mass of electric vehicle reducer. Through examples, relevant program is compiled with matlab software. It is obtained that there is a distribution method for gear ratio of the electric vehicle reducer.